SURGICAL TACTICS IN THE DIEULAFOY’S LESION OF RARE LOCATION - V. P. Zemlyanoy; B. V. Sigua; D. V. Gurjyi; I. A. Melendin; D. G. Berest; S. A. Vinnichuk (Неотложная медицинская помощь, 2018)
Abstract The given clinical example demonstrates the possibility of diagnosis and surgical treatment of Dieulafoy’s lesion with rare location (cecum in this case) when endoscopic hemostasis cannot be adequately performed. The manifestation of the disease is caused by the use of dual antiplatelet therapy after installation of stents into coronary arteries for unstable angina.